REALISASI TINDAK TUTUR REMAJA ALAYERS PADA AKUN FACEBOOK - Irawati Bangun; Ridwan Hanafiah; Thyrhaya Zein (Balai Bahasa Sumatera Utara, 2019)
Alay language is one of the new languages that has a negative impact on the existence of Indonesian. because it violates the good and right Indonesian norms and ethics. The purpose of this study is to find out how the realization of Alayers teenage speech acts on Facebook accounts with a sociolinguistic approach. This research is a type of qualitative research that applies content analysis research. The data in this study are words, phrases and sentences in Alay language. Data was sourced from uploading statuses and comments from Alayers in the group A collection of middle / high school kids looking for girlfriends and friends. To collect data in this study, researchers used data collection techniques, namely, observation and substitution techniques. Furthermore, the data was analyzed using the interactive model analysis techniques of Miles, Huberman and Saldana. Based on the results of the study it was found that out of 27 data obtained by researchers, it was found that there were 20 speech acts used by teenagers in uploading their status on Facebook, 5 speech acts in the form of complaints, and 2 more as speech acts in the form of praise. Alayers' teenage talk on Facebook accounts is realized through vulgar sentences and added images and videos containing pornography. The factors that influence adolescent Alayers speech acts on Facebook accounts are: a) Technological sophistication factor; b) Environment and c) Want to get recognition.